2016
DOI: 10.1117/1.jbo.21.7.075003
|View full text |Cite
|
Sign up to set email alerts
|

Light distortion and spherical aberration for the accommodating and nonaccommodating eye

Abstract: To evaluate how different amounts of induced spherical aberration (SA) affect the light distortion (LD) phenomena, tests were performed using an experimental device to measure the distortion (haloes, glare, and so on) of a point source. To simulate the effect of SA, eight different phase plates between +0.300 and −0.300  μm of SA for a 5-mm aperture were used in a random and double-masked experimental design. Measurements were performed at a distance of 2 m in a darkened room in 10 eyes of five subjects with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
2
13
1
Order By: Relevance
“…On one level, this may explain the differences observed in LD between dominant (center-distance design) and non-dominant (center-near design). However, in contrast to the results of Macedo-de-Araujo et al [29], it was found that the increase in LD was greater with the center-near design (more negative SA) compared to center-distance design. This may be due to the difference for SA induced by multifocal design compared to those experimentally induced in previous studies.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…On one level, this may explain the differences observed in LD between dominant (center-distance design) and non-dominant (center-near design). However, in contrast to the results of Macedo-de-Araujo et al [29], it was found that the increase in LD was greater with the center-near design (more negative SA) compared to center-distance design. This may be due to the difference for SA induced by multifocal design compared to those experimentally induced in previous studies.…”
Section: Discussioncontrasting
confidence: 96%
“…Macedo-de-Araújo et al 29 reported that the induction of +0.15 μm spherical aberration (SA) leads to an increase between 10 and 20% in light disturbance index (LDI). Considering that the mean induced SA by multifocal CL are in that order of magnitude, the sample size required was 18 subjects, to warrant an 80% power (type II error risk of 20%) and to detect 10% differences in LDI between follow-up visits, for a statistical significance level of p = 0.05 (type I error risk of 5%).…”
Section: Samplementioning
confidence: 99%
“…We cannot ensure that the LD parameter reflects specifically the haloes, ghost images, starburst, and glare reported subjectively by the patient. However, we have reported in a recent study that the system is sensitive to the photic phenomena induced when we artificially incorporate different amounts and sign of HOA [18]. Although we cannot quantify each one of the photic phenomena, we consider that such effects are well reflected in the short-term measurements in this study and that adaptation takes place to reduce the size of the LD overtime in the middle [14] and longer term (present study), in agreement with transient subjective complaints expressed by the patient in the clinical setting [13].…”
Section: Discussionmentioning
confidence: 99%
“…It consists of an array of 240 1 mm wide LEDs distributed radially at 15° intervals over 160 mm, with a linear separation of 10 mm around a central 5 mm white LED that acts as glare source, as previously described [17, 18, 20]. The system is controlled by a custom-made software that interfaces with the patient to detect the peripheral stimuli seen and discriminate them from those hidden by the central glare source.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation